PENGEMBANGAN MEDIA PEMBELAJARAN ENGKLEK BERBASIS CULTURALLY RESPONSIVE TEACHING DALAM PEMBELAJARAN IPAS DI KELAS IV SD NEGERI TAMBAKSOGRA 2: Penelitian Research and Development (R&D) - Luthfiyah Mufidah; Aji Heru Muslim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The current advancement and curriculum demands require teachers to be innovative in managing learning processes. Developing learning media is a key step toward achieving educational objectives effectively. This study aimed to develop Engklek learning media integrated with the Culturally Responsive Teaching (CRT) approach to facilitate material comprehension and enhance stundent engagement in the topic of Indonesia’s Cultural heritage. This research employed a Research and Development (RD) methodology using the ADDIE model, collecting data through media validators, material validators, teacher response questionnaires, and student response questionnaires. The Culturally Responsive Teaching-based Engklek learning media was developed at SD Negeri 2 Tambaksogra, Banyumas, Central Java. The media validator results indicated of score 98%, the material validator results were 80%, the teacher response score was 94%, and the student response score was 98%, indicating tha this media is highly suitable for use in the learning process.